Function of Swearing Expressions on Women's Instagram Accounts - Wahyuni, Wika (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research is motivated by differences in the language varieties of women and men in society. The difference focused on in this research is the swearing expressions used by female users on Instagram. Society's views and language theories related to gender show that the use of swear words by men can be considered normal, whereas it is very bad if used by women. The problem to be answered in this research is the function and reasons for the expression of swear words in women's writing on Instagram accounts. The target of this research was 115 quotes (status and comments) written by female Instagram users. The theory used to study the function of swear expressions is Anderson and Trudgill's theory. Data was collected using observation and documentation methods. Data were analyzed using the content analysis method which includes data reduction, data presentation, and drawing conclusions. Data is presented in the form of tables and narrative text. Based on the results of the analysis, the functions of swear expressions found were expletive function, humorous function and auxiliary function. Other findings are the reasons for the use of swearing expressions by women on Instagram, namely 1) swearing is seen as the most effective way to express feelings of dislike, anger, disgust, disappointment, etc. towards the physique or actions of celebrities seen through Instagram social media accounts, 2) social media is a forum for indirect communication, so that communication activities are carried out remotely, the speaker and the interlocutor do not meet face to face, do not interact face to face, do not even know each other or have met before, this condition causes women to dare to write harsh words because they think they will not meet so there is no need to feel guilty, and 3) there are examples of public figures or celebrities who are accustomed to using swear words on the basis of freedom of expression